Coatings Formulation An International Textbook - Müller, Bodo 1954-; Poth, Ulrich (European Coatings, 2017)
Your comprehensive knowledge base when it comes to the formulation of paints and coatings: already in its 3rd edition, this book imparts the composition of coatings clearly, placing special emphasis on the base binder in each type. Advice on specific formulations is then given before formulation guidelines are analysed. Examples of how to develop a real-life paint formulation round off this useful standard work